2009
DOI: 10.1002/adsc.200900133
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐Stabilized Phosphenium Adducts as New Efficient and Immobilizing Ligands in Palladium‐Catalyzed Alkynylation and Platinum‐Catalyzed Hydrogenation in Ionic Liquids

Abstract: Abstract:The straightforward synthesis of a new donor-stabilized phosphenium ligand 3d by addition of bromodifurylphosphine to 1,3-dimethylimidazolium-2-carboxylate 1 is described. The obtained ligand exhibits a very strong p-acceptor character, comparable to that of triphenyl phosphite [PA C H T U N G T R E N N U N G (OPh) 3 ] or of tris-halogenophosphines, with a n CO (A 1 ) at 2087 cm À1for its nickel tricarbonyl complex. This ligand, as well as the related 3a which was obtained from chloroA C H T U N G T R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…These ligands have proven to be highly effective in Pd-catalyzed aryl alkynylation reactions as well as in Pt-catalyzed hydrogenation reactions in ionic liquids. [58] Furthermore, these ligands display remarkable coordination properties (see section on ligand substitution reactions later).…”
Section: Steric and Electronic Properties Of Ionic Phosphine Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…These ligands have proven to be highly effective in Pd-catalyzed aryl alkynylation reactions as well as in Pt-catalyzed hydrogenation reactions in ionic liquids. [58] Furthermore, these ligands display remarkable coordination properties (see section on ligand substitution reactions later).…”
Section: Steric and Electronic Properties Of Ionic Phosphine Ligandsmentioning
confidence: 99%
“…[53] Andrieu et al reported on cationic imidazolium-2-phosphines 19 a-d, which can be described as phosphenium cations stabilized by a N-heterocyclic carbene donor base. [57,58] The lone pair on the phosphorus atom is not delocalised into the imidazolium fragment and thus remains available for coordination to a metal center. By measurement of the CO stretching frequency in the corresponding complexes [Ni(CO) 3 L] (L = 19 a-d), it was established that this remarkable class of phosphine ligands act as very weakly s-donat- ing and/or very strongly p-accepting ligands (Table 2, entries 39-42).…”
Section: Steric and Electronic Properties Of Ionic Phosphine Ligandsmentioning
confidence: 99%
“…38 Such ligands L20a-c 39 and L20d could be obtained directly from 1,3-dimethylimidazolium-2-carboxylate (Schemes 31 and 32, respectively). …”
Section: Sonogashira Reactionmentioning
confidence: 99%
“…Another approacht oi midazoliumyl-substituted P III compounds relies on the use of the imidazolium 2-carboxylate 83 as NHC precursor. [68,69] The reaction of 83 with one equivalent of R 2 PCl (R = Ph, iPr,C y) affords the chloride salts of cations 84 a-c + under release of CO 2 (Scheme 24). The anion is exchanged to PF 6 À by treatmentw ithK [PF 6 ].…”
Section: G)mentioning
confidence: 99%